2020
DOI: 10.3390/diagnostics10070461
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical Performance of a New Particle-Enhanced Method for Measuring Procalcitonin

Abstract: We report the analytical performances of two particle-enhanced (PETIA) methods for measuring procalcitonin (PCT), the Diazyme PCT and the new DiaSys PCT assay, and their concordance of values with BRAHMS PCT Kryptor©. The total imprecisions onto two control levels and one serum pool were for DiaSys 5.42%, 3.3% and 7.53% and for Diazyme 10.7%, 2.9% and 13.23%, respectively. The limit of blank, limit of detection and limit of quantification were under the 0.25 cut-off for the two methods. The linearity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Taking for granted that deviations in the absolute quantification between measurement methods will exist, an important question follows: how crucial is the absolute CRP quantification itself, in terms of its clinical utility as a biomarker for antibiotic prescription decision support? From a clinical perspective, and for biomarkers like CRP-but also others like procalcitonin-randomized controlled studies have shown that it is efficient to stratify patients in ranges (zones) defined above or below concentration cutoff values to guide antibiotic prescriptions [10][11][12][13]45,46]. The cutoffs and ranges may differ depending on the clinical condition (e.g., RTIs, tropical infections, and sepsis), age group (elderly versus children or infants), healthcare settings (primary care, emergency unit, and intensive care unit), etc.…”
Section: The Clinical Relevancementioning
confidence: 99%
“…Taking for granted that deviations in the absolute quantification between measurement methods will exist, an important question follows: how crucial is the absolute CRP quantification itself, in terms of its clinical utility as a biomarker for antibiotic prescription decision support? From a clinical perspective, and for biomarkers like CRP-but also others like procalcitonin-randomized controlled studies have shown that it is efficient to stratify patients in ranges (zones) defined above or below concentration cutoff values to guide antibiotic prescriptions [10][11][12][13]45,46]. The cutoffs and ranges may differ depending on the clinical condition (e.g., RTIs, tropical infections, and sepsis), age group (elderly versus children or infants), healthcare settings (primary care, emergency unit, and intensive care unit), etc.…”
Section: The Clinical Relevancementioning
confidence: 99%
“…However, not all assays commercially available take part in this harmonization effort, thus there is currently no commonly agreed reference material for all available PCT immunoassays at the international level. Therefore, the need for a new reference system based on higher order reference materials and/or a higher-order reference method to achieve global standardization/harmonization of PCT results worldwide has been pointed out in a number of studies [56][57][58][59]64,65].…”
Section: Procalcitonin and Its Current Measurement Proceduresmentioning
confidence: 99%